Pelatihan dan Bimbingan Digital Marketing Bagi Pelaku UMKM di Kelurahan Kepanjen Lor Kota Blitar - Nabigus Thoriq Harasta; Sugito Sugito (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Food is a basic human need, therefore, the food industry is an industry that will always grow, at least following population growth. It is not surprising that the food industry, especially small-scale industries, has sprung up to meet this demand. As a form of community service, the East Java UPN "Veteran" KKN-T 26 group invites and educates the public to do entrepreneurship, especially digitally using social media by creating “Singkong Crispy” Training and Online Marketing programs. This program is an activity that aims to increase people's creativity in entrepreneurship. The target of this program is the surrounding community, especially the women of RT 01 RW 05 in the Kepanjenlor Village, Blitar City. The methods used in this program are lectures, demonstrations and practicum. The results of this activity participants can receive knowledge and can develop potential in entrepreneurship through “Singkong Crispy”.